2022
DOI: 10.18063/ijb.v9i2.654
|View full text |Cite
|
Sign up to set email alerts
|

The first 3D-bioprinted personalized active bone to repair bone defects: A case report

Abstract: The repair and reconstruction of bone defects are still major problems to be solved in the field of orthopedics. Meanwhile, 3D-bioprinted active bone implants may provide a new and effective solution. In this case, we used bioink prepared from the patient’s autologous platelet-rich plasma (PRP) combined with polycaprolactone/β-tricalcium phosphate (PCL/β-TCP) composite scaffold material to print personalized PCL/β-TCP/PRP active scaffolds layer by layer through 3D bioprinting technology. The scaffold was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Due to their properties, some CaPs such as HAp, tricalcium phosphate (TCP) and amorphous calcium phosphate (ACP) are widely used as biomaterials for bone repair. At the same time, other CaPs (dicalcium phosphate anhydrous (DCPA), dicalcium phosphate dihydrate (DCPD) and octacalcium phosphate (OCP)) were discovered earlier but only recently attracted the attention of scientists for applying them in 3D (c) PCL/β-TCP scaffolds with the patient's autologous platelet-rich plasma [13]; (d) 3D-printing process of chitosan/alginate/HAp scaffold for potential cartilage regeneration [14]. (Refs.…”
Section: Calcium Phosphates Used In Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their properties, some CaPs such as HAp, tricalcium phosphate (TCP) and amorphous calcium phosphate (ACP) are widely used as biomaterials for bone repair. At the same time, other CaPs (dicalcium phosphate anhydrous (DCPA), dicalcium phosphate dihydrate (DCPD) and octacalcium phosphate (OCP)) were discovered earlier but only recently attracted the attention of scientists for applying them in 3D (c) PCL/β-TCP scaffolds with the patient's autologous platelet-rich plasma [13]; (d) 3D-printing process of chitosan/alginate/HAp scaffold for potential cartilage regeneration [14]. (Refs.…”
Section: Calcium Phosphates Used In Tissue Engineeringmentioning
confidence: 99%
“…Gelatin methacryloyl (GelMA), gelatin MC3T3-E1 subclone 4 mouse calvaria osteoblast [93] Hydroxyapatite-magnetic iron oxide nanoparticles Gelatin methacryloyl (GelMA) Human PDLFs and human osteoblasts (hOBs) [94] α-TCP Gelatin methacrylate (GelMA) Mouse calvaria-derived preosteoblast cell line (MC3T3-E1) [95] Amorphous calcium phosphate micro/nanoparticles Gelatin methacrylate (GelMA) MC3T3, adipose-derived mesenchymal stem cells (AdMSC) [96] β-tricalcium phosphate Polycaprolactone (PCL) The patient's autologous platelet-rich plasma (PRP) [13] β-tricalcium phosphate Collagen…”
Section: Hydroxyapatite Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, clinical trials showed positive effects of bone scaffolds enriched with PCs. Hao et al [219] developed a personalized 3D-printed scaffold composed of PCL, β-TCP and the patient's autologous PRP for the reconstruction of the bone defect after the resection of the tibial tumor. In this study, the authors presented a case report involving a 16-year-old patient for whom personalized therapy using PCL/β-TCP scaffold + PRP turned out to be an effective method of treatment after tumor resection.…”
Section: Mineralized Collagen-based Biomaterialsmentioning
confidence: 99%
“…Under the irradiation of 808-nm near-infrared light, it can quickly stop bleeding and coordinate human bone marrow mesenchymal stem cell osteogenesis when the temperature reaches around 42 °C. Considering the diversity of bone defect shapes, 3D bioprinting technology provides a personalized design of active scaffolds to repair and reconstruct the defects of weight-bearing bone [ 105 ].…”
Section: Hemostatic Biomaterials For Bone Repair Applicationsmentioning
confidence: 99%